Updated recommendations for diagnosis and treatment of multiple myeloma in Switzerland (Swiss Medical Weekly, 2025)
Multiple myeloma is a malignant disease characterised by the clonal proliferation of plasma cells. Since the last update of the Swiss recommendations for the diagnosis and treatment of multiple myeloma in 2019, the therapeutic landscape has evolved significantly, with the development of new monoclonal antibodies, novel combination therapies, and the introduction of T-cell-redirecting treatments such as bispecific antibodies and CAR T-cell therapy. This article summarises the current diagnostic procedures and therapeutic recommendations in Switzerland.